Developing the performance of public education departments in the Kingdom of Saudi Arabia in light of strategic management - Al-Otaibi, Mashael Asir; Al-Yousef, Jawaher Khalid; Al-Maalawi, Haifa Khalif (Journal of Educational and Psychological Sciences, 2025)
The research aimed to identify the reality of the performance of public education departments in the Kingdom of Saudi Arabia in light of strategic management and its development scenarios. The research adopted the content analysis methodology and the prospective approach. The research community consisted of the document on the organizational structures of public education departments issued by the Ministry of Education, the document on operational plans for public education departments in the Kingdom, and previous literature. The research sample consisted of the unified organizational structure of public education departments, the latest edition for the year 1445 AH, and the operational plans for five public education departments in the Eastern Province, Al-Jawf, Riyadh, Asir, and Al-Baha. The research relied on the content analysis tool to analyze the content of education departments’ documents in the Kingdom. The results showed that the organizational structure of education departments in the Kingdom is characterized by centralization in decision-making and task implementation; Which causes it to lose flexibility in managing its affairs and work, and hinders its rapid response to internal and external changes, and that many education departments have not announced the vision and mission on the official websites and accounts, in addition to the ignorance of its employees, and the priorities have not appeared sufficiently through monitoring indicators of their achievement in operational plans, and the organizational structure and operational plans of education departments are in dire need of reconsidering their reality, outputs, and the extent of their impact on the procedures of public education departments in the Kingdom. Based on the results, the study recommended developing the performance of public education departments in the Kingdom and adopting modern methods and practices in work environments.
Keywords: Developing administrative performance; education departments; strategic management; scenarios; future studies